FAMILY CENTERED NURSING CARE (FCN) MODEL IN SNH (Non-Hemorrhagic Stroke) PATIENTS - Al-Mahdi, Fadhil; Negara, Candra Kusuma; Basid, Abd; Dalle, Juhriyansyah (Sean Institute, 2022)
The process resulting from chronic diseases is the inability to carry out activities independently and freely, so a caregiver who provides a series of treatments is needed. The optimal role of caregivers requires an appropriate approach to improve these abilities. One model that can be applied to caregivers of stroke patients is family-centered care. The FCC model applied to stroke patients can build a system of collaboration, focus on the strengths and sources rather than the weaknesses of the family, recognize the family's expertise in caring for patients, build empowerment rather than dependence, increase more information sharing with patients, caregivers and health services than information only known to professionals, create flexible and non-rigid programs. This study aims to develop an FCC model for caregivers who treat stroke patients at home and can be used as a guide by nurses and caregivers in treating stroke patients at home. This research design is action research, which consists of the stages of the survey, planning, acting, observing, and reflecting. The data collection method was carried out through FGDs, the distribution of questionnaires, and the observation of participants. The participants who contributed to this study were 31 caregivers of stroke patients—data analysis using quantitative and qualitative methods. Qualitative data were obtained through FGD results and observation results. In contrast, quantitative data was collected through the dissemination of FCC questionnaires, assessing the swallowing status of stroke patients, and observing results were analyzed using descriptive statistical tests. This research has produced an FCC Model, a reference in treating stroke patients with dysphagia disorders. It positively impacts increasing skills, the ability to practice swallowing, and assessing swallowing ability in treating stroke patients with dysphagia disorders. Another impact of developing the FCC Model at the Center is that caregivers can apply FCC values when treating stroke patients with dysphagia